Understanding halal supply chains: ensuring integrity in the global halal food market - Mohamad Salleh, Musdiana; Harun, Etty Harniza (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
Halal, an Arabic term meaning "permissible" or "lawful," refers to products and practices permissible according to Islamic law. The global halal food market has grown significantly in recent years, driven by an increasing Muslim population and rising consumer awareness of Islamic dietary rules (Haleem et al., 2020). As a result, ensuring the integrity of halal products throughout the supply chain has become crucial as Muslim consumers are increasingly concerned about the authenticity of halal-certified products. This paper explores the critical role of halal supply chains in maintaining integrity within the global halal food market, focusing on the importance, problems, and methods for developing halal supply chains.